2021
DOI: 10.3389/fphar.2021.755140
|View full text |Cite
|
Sign up to set email alerts
|

Buddleoside-Rich Chrysanthemum indicum L. Extract has a Beneficial Effect on Metabolic Hypertensive Rats by Inhibiting the Enteric-Origin LPS/TLR4 Pathway

Abstract: As the number of patients with metabolic hypertension (MH) is increasing, there is an essential require for global measures to prevent and treat MH. Flavonoids such as buddleoside (BUD) from Chrysanthemum indicum L. are the main pharmacological components of cardiovascular activities. Previous studies have suggested that the buddleoside-rich Chrysanthemum indicum L. extract (BUDE) can reduce blood pressure in spontaneously hypertensive rats (SHR). However, its effect on MH and how it works remains to be resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…ET-1 and TXB 2 have vasoconstrictive effects, and their elevated levels are an important cause of hypertension [ 55 , 56 ]. In the present study, vascular endothelial injury, increased the plasma levels of ET-1 and TXB 2 , and decreased levels of NO and PGI 2 were found in rats with MH, consistent with previous results [ 4 , 5 ]. PNFS corrected the imbalance of vasoactive substance levels in rats with MH and improved vascular histopathological changes (hyperplasia and disorganization of vascular smooth muscle cells, and misaligned and interrupted endothelial cells with detachment).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…ET-1 and TXB 2 have vasoconstrictive effects, and their elevated levels are an important cause of hypertension [ 55 , 56 ]. In the present study, vascular endothelial injury, increased the plasma levels of ET-1 and TXB 2 , and decreased levels of NO and PGI 2 were found in rats with MH, consistent with previous results [ 4 , 5 ]. PNFS corrected the imbalance of vasoactive substance levels in rats with MH and improved vascular histopathological changes (hyperplasia and disorganization of vascular smooth muscle cells, and misaligned and interrupted endothelial cells with detachment).…”
Section: Discussionsupporting
confidence: 93%
“…MH is characterized by multiple metabolic disorders, often leading to cardiovascular and cerebrovascular complications, and the pathological mechanisms behind its development are complex [ 4 ]. Some scholars suggested that irrational dietary habits are responsible for the initiation of MH [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other activities of Chrysanthemum flavonoids are also intriguing. Linarin and scutellarein displayed anticancer activity ( Jung et al, 2019 ; Li et al, 2020 ); buddleoside reduced blood pressure in spontaneously hypertensive rats by inhibiting the vascular TLR4/MyD88 pathway and improving vascular endothelial function ( Wang et al, 2021c ); Acn-7-O-β-D-rutinoside prevented dexamethasone-evoked muscle atrophy via the Akt/mTOR pathway and decreasing the mitochondrial respiration ( Lee et al, 2021 ).…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) is the most common gastrointestinal disease and is classified as ulcerative colitis (UC) and Crohn’s disease (CD) . More than 6.8 million people worldwide suffer from IBD, with approximately 1% of the world’s population expected to be affected by the disease by 2030. , Despite the unclear pathogenesis of IBD, studies have found a strong correlation between the consumption of a Western diet high in fat and refined sugar, and the development of IBD. High-fat diets have been shown to exacerbate DSS-induced colitis, which can be alleviated by adding fiber-rich foods. A clear causal relationship has also been demonstrated that there is between the intake of fructose or glucose and the development of IBD, with the gut microbiota playing a mediating role. , The gut microbiota, comprising diverse and dynamic microbial communities inhabiting the gastrointestinal tract, plays a crucial role in host health and disease, and is considered to be an essential pathogenetic mechanism of colitis. , When the gut microbiota undergoes dysbiosis, the gut microbial metabolite lipopolysaccharide (LPS) may be produced excessively, and impairment of the integrity of the intestinal barrier leads to increased penetration of LPS . In this case, LPS activates Toll-like receptor 4 (TLR4) on host cells, leading to the activation of myeloid differentiation factor 88 (MyD88) and nuclear factor kappa-B (NF-κB) expression, which induces the production of pro-inflammatory cytokines, thereby exacerbating intestinal inflammation .…”
Section: Introductionmentioning
confidence: 99%